Characterization of patients receiving palliative care in a private non-hospital unit in El Salvador - Lopez Saca, José Mario (2020)
In El Salvador, access to palliative care is limited. In July 2013, he started a private support and symptom control unit in palliative care. They care for cancer and non-cancer patients at three levels: outpatient consultation, hospitalization in private centers and home care. The objective of this study is to describe the demographic and clinical characteristics of the population attended from January 2014 to December 2016 as the first experience of private palliative care in San Salvador.It is an observational, retrospective and descriptive study, using the population census and clinical records. Where sociodemographic and clinical variables of the patients were collected in an initial assessment by the palliative doctor.The total of patients was 125. Being 56.8% women with an average age of 72 years. 68% of patients live in San Salvador. 14.4% have private health insurance. 68% received a home consultation. 86.4% of the patients attended suffered from oncological diseases. The most frequent symptoms: weakness 90.4%, lack of appetite 88.8% and pain 76%. The most widely used opioid was morphine 28.8% followed by tramadol 17.6%, oxycodone 8% and fentanyl 8%. 12.8% required palliative sedation. The patients were referred by doctors in 52.8% and by relatives 47.2%.We present the characteristics of the patients cared for in the private unit and whose results show that when palliative care cares for its principles and basic elements of work, the results are similar to other units in the rest of the world.